First detection of Mycobacterium triplex in Latin America. Issue 1 (March 2016) - Campos, Carlos Eduardo Dias; Dias, Cláudia Fontoura; Unis, Gisela; de Souza Caldas, Paulo Cesar; Redner, Paulo; de Carvalho, Luciana Distásio; Gomes, Ana Paula Chaves Sobral; Ribeiro, Marta Osório; Montes, Fátima Cristina Onofre Fandinho; Tortoli, Enrico; Ramos, Jesus Pais
Abstract: In this study we describe the first isolation of Mycobacterium triplex in Latin America. This species causes infections in humans, with very few reports from around the world. We isolated two sputum specimens of a patient with a 6-year history of human immunodeficiency and tuberculosis treatment failure. All tests used confirmed M. triplex and the patient responded well to drug therapy for 18 months.